If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + -4 = -7 + x Combine like terms: -9 + -4 = -13 -13 = -7 + x Solving -13 = -7 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -13 + -1x = -7 + x + -1x Combine like terms: x + -1x = 0 -13 + -1x = -7 + 0 -13 + -1x = -7 Add '13' to each side of the equation. -13 + 13 + -1x = -7 + 13 Combine like terms: -13 + 13 = 0 0 + -1x = -7 + 13 -1x = -7 + 13 Combine like terms: -7 + 13 = 6 -1x = 6 Divide each side by '-1'. x = -6 Simplifying x = -6
| 6x^2+36x+18=0 | | 7(a-7)+18=5(a-5) | | 6(2x+-1)+3=x+7 | | 3(6n-4)+9n= | | 3x^2+72x+402=0 | | 5+3x+(-3)=x-(-4) | | 9x-8=6x+37 | | 5x-(-21)=x-(-19) | | -58=y/4 | | ((6-14)+4)*4= | | -58=-6y | | 5x-(21)=x-(-19) | | 14e^2+4x=112 | | x-(-5)=6x+10 | | 42/-6 | | a+b-a+2b= | | 1/5x+3=14 | | 4x^2-8x-77=0 | | 3x-(-1)=-16 | | 5+2y=6 | | 4x+6=24-2 | | 256*12x= | | 256*20= | | 5w-7w=4 | | 4z=1.8+3.8 | | 10/7*4 | | X-5x+3x-9x= | | 1.4(5x-.1)= | | 5/6k=7 | | -12-16*4= | | 4(z+6)-26= | | 4x/7x+28 |